Study Of The Extraction Of Cobalt(ii) From Sulphate Medium By Using Capric Acid Dissolved In Chloroform - Slimani, A.; Barkat, D. (University of Eloued جامعة الوادي, 2017)
In this work we have first investigated the extraction of cobalt(II) from sulphate medium using capric acid dissolved in chloroform and then the effect of other diluents on the extraction process at 25°C. This study aims to understand the behaviour followed by this metal or, in other words, find its stoichiometry at the end of the extraction. This deportment is strongly dependent on many parameters like pH of the aqueous solution, acid concentration and the nature of the solvent. Each one of these parameters will be discussed. Temperature is another parameter that will be studied in this work. At the end of this research, we have found that stoichiometry of Co(II) complex is of the type CoA2(HR)2 (HR is an abridgment of capric acid). The equilibrium constant Kex and the thermodynamic parameters ΔH°, ΔS°, and ΔG° have been evaluated.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 01
Keywords: Capric acid; Cobalt(II); Sulphate medium; Solvent polarity, Temperature effect.